KEBUGARAN JASMANI PADA MAHASISWA OBESITAS POLTEKKES KEMENKES TASIKMALAYA - Aryanti, Dewi; Ambarwati, Tritania (Jurusan Keperawatan Gigi Poltekkes Kemenkes Tasikmalaya, 2020)
Background: Physical fitness is an important issue for every individual including students. Physical fitness is closely related to the condition of obesity and the level of physical activity. Some Poltekkes Kemenkes Tasikmalaya students have conditions of obesity and low physical activity. The purpose of this study is to get a description of physical fitness in obese students in the Polytechnic of the Ministry of Health Tasikmalaya. Method: This study used a descriptive non-experimental design. The total sample of subjects in this study were 100 regular students (75 female and 25 male) who had been screened for obesity with a body mass index (BMI) more than 24.9. After filling in general demographic and anthropometric data, the sample then underwent physical fitness measurements using the Balke technique. Data were analyzed using central tendency values, proportions / percentages for physical fitness level variables. Results: The results of this study showed that 100% of obese students in the Poltekkes of the Ministry of Health Tasikmalaya had a very low level of physical fitness. This condition requires the support and attention of relevant individuals and the Poltekkes Ministry of Health of the Ministry of Health Tasikmalaya to prevent more severe risks.